Reimagining Paradise: Postcolonial Ecocriticism in Selected Hawaiian Literature - Indriyanto, Kristiawan; Suryaningsih, Sukarni; Sriastuti , Anna (Journal of English Studies, 2024)
The contemporary Hawaiian literary landscape provides a profound lens for deconstructing the pervasive paradise trope associated with the islands. This deconstruction reveals a postcolonial Hawaii marked by environmental shifts and tourist-driven development exploiting the paradise myth. This paper reads contemporary Hawaiian literature, Alan Brennert’s Moloka’i, Honolulu and Kristiana Kahakauwila’s This is Paradise, to contextualize the consequences of modernity and exploitation of Native Hawaiians and immigrant populations. The narratives juxtapose the idealized perception of Hawai’i as a tropical paradise with the harsh realities faced by plantation laborers, lepers, and marginalized Indigenous within the tourist industry. This analysis highlights the disparity between the idealized portrayal of Hawai’i and the challenging conditions marginalized groups face. These narratives serve as critical instruments in dismantling the paradisal myth, delineating the historicity of Hawai’i as a postcolonial space.